The Influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on Share Prices at PT Indofarma Tbk - Budi, Andri Setia; Rahmi, Palupi Permata; Karamang, Ezra (International Journal of Business, Management and Economics, 2024)
This research aims to analyze the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on the Share Prices of PT Indofarma Tbk for the 2012-2022 period. The independent variables used are Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA), while the dependent variable is Share Prices. These data were then analyzed using the multiple linear regression method involving the t statistical test (partial), the f statistical test (simultaneous), and the coefficient of determination test. The research results show that the Current Ratio (CR) and Return on Assets (ROA) partially have a positive and significant effect on Share Prices. Debt to Equity Ratio (DER) partially has a negative and significant impact on Share Prices. Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) simultaneously have a positive and significant effect on Share Prices. The contribution of the independent variables (Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) to Share Prices reached 68.6%.